The HYPONATREMIA IN ACUTE MYOCARDIAL INFARCTION AND SHORT-TERM CLINICAL OUTCOME: A CROSS-SECTIONAL STUDY - NAVEEN KUMAR G; ANANDI C; SEENIVASAN M (Asian Journal of Pharmaceutical and Clinical Research, 2025)
Objectives: Neurohumoral activation in acute myocardial infarction (MI) causes hyponatremia and is associated with poor outcome. We aimed to establish a relationship between hyponatremia in acute ST-elevation MI (STEMI) and its complications. Methods: Patients with acute STEMI were included. The patients were monitored for serum sodium at admission; at 24, 48, and 72 h; and echocardiographic evaluation at admission and at 72 h. Complications such as left ventricular (LV) failure and mortality during hospital stay were noted. Results: In the acute setting of STEMI, hyponatremia was observed in 86% of patients aged >60 years (p=0.001). In patients with moderate LV dysfunction, 91% had hyponatremia at 24 h after admission, with persistent hyponatremia in 66.7% at 72 h (p=0.02). Within 24 h of admission, when the patient had normal serum sodium, the risk of complications was 16%, with mild hyponatremia the risk was 66.7%, with moderate hyponatremia the risk was 85.7%, and with severe hyponatremia the risk was 100% (p=0.001). Conclusion: Elderly individuals are prone to hyponatremia following acute MI. LV dysfunction is associated with hyponatremia following MI. Moderate-to-severe hyponatremia is associated with a high risk of complications.